4x - 3y = 6
4x - 3y - 4x = - 4x + 6
- 3y = - 4x + 6
- 3y / - 3 = - 4x / - 3 + (6 / - 3)
y = 4/3x +( - 2)
y = 4/3x - 2
- - - - - - - - -s-
2007-05-01 07:59:07
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
With only one equation, you can only change this to give x in terms of y.
This would be y = 4/3 x - 2, or the slope-intercept form.
Steps to do this :
Subtract 6 from both sides to get 4x - 3y - 6 = 0
Add 3y to both sides to get 4x - 6 = 3y
Divide by 3 to get the y alone and get 4/3 x - 2 = y
2007-05-01 14:49:15
·
answer #2
·
answered by Don E Knows 6
·
0⤊
0⤋
4x-6=3y 4/3x-2=y
2007-05-01 14:20:49
·
answer #3
·
answered by dwinbaycity 5
·
0⤊
0⤋
y = 4x-6 / 3
2007-05-01 14:27:00
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
3y = 4x - 6
y = (4/3) x - 2
2007-05-01 14:20:53
·
answer #5
·
answered by Como 7
·
0⤊
0⤋
y= (4/3)x - 2
2007-05-01 14:21:13
·
answer #6
·
answered by Will S 1
·
0⤊
0⤋
4x -3y = 6
-3y = 6 -4x
y = (6 -4x)/-3
or
y = -(6 -4x)/3
y = (4x -6)/3
or
y = 4x/3 -2
2007-05-01 14:34:12
·
answer #7
·
answered by Necromancer of Egypt 5
·
0⤊
0⤋
( 4x - 6 ) / 3
2007-05-01 14:20:47
·
answer #8
·
answered by Tommy 2
·
1⤊
0⤋
x and y both equal 6
2007-05-01 14:21:32
·
answer #9
·
answered by MFREEBIRD 3
·
0⤊
0⤋